IMPLEMENTATION OF BLENDED LEARNING IN IMPROVING STUDENTS SELF EFFICACY - Amini, Amini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The implementation ofBlended Learningin students towardsself-efficacy,turns out to have a big influence; Its role is important enough to makestudentshavehighself-confidence.Byconstructinghighself-efficacyinindividual students, this will grow and generate achievement, enthusiasm andthe ability to deal with difficult conditions in the learning process. This is goodfor students to have in the process of seeking knowledge.In his research, theresearcher explained the results of the implementationofBlended Learningon students'Self Efficacy. It also explains how important the existence ofSelfEfficacyis in individual students in their learning process.